2020
DOI: 10.1093/ofid/ofz554
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Management of Uncomplicated Skin and Soft Tissue Infections in 34 Veterans Affairs Medical Centers: A Medication Use Evaluation

Abstract: Background Skin and soft tissue infections (SSTIs) are a key antimicrobial stewardship target because they are a common infection in hospitalized patients, and non-guideline-concordant antibiotic use is frequent. To inform antimicrobial stewardship interventions, we evaluated the proportion of veterans hospitalized with SSTIs who received guideline-concordant empiric antibiotics or an appropriate total duration of antibiotics. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
3
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
5
3
2
2
Order By: Relevance
“…The provision of appropriate antibiotics in a critically ill patient population may be important to optimise patient outcome and minimise antibiotic‐associated harms. Previous studies have identified that guideline‐concordant antibiotic prescribing reduces mortality in patients with community‐acquired pneumonia, 22,23 intra‐abdominal infections 24 but not skin and soft tissue infections 25 . The current study did not replicate these findings whereby inappropriate antibiotics did not increase patient mortality, which may be due to the heterogeneity in patient comorbidities as we demonstrated, as well as the site of infection 26–28 and microbiological factors 29 that each influence mortality outcomes.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The provision of appropriate antibiotics in a critically ill patient population may be important to optimise patient outcome and minimise antibiotic‐associated harms. Previous studies have identified that guideline‐concordant antibiotic prescribing reduces mortality in patients with community‐acquired pneumonia, 22,23 intra‐abdominal infections 24 but not skin and soft tissue infections 25 . The current study did not replicate these findings whereby inappropriate antibiotics did not increase patient mortality, which may be due to the heterogeneity in patient comorbidities as we demonstrated, as well as the site of infection 26–28 and microbiological factors 29 that each influence mortality outcomes.…”
Section: Discussioncontrasting
confidence: 81%
“…Previous studies have identified that guideline-concordant antibiotic prescribing reduces mortality in patients with community-acquired pneumonia, 22,23 intra-abdominal infections 24 but not skin and soft tissue infections. 25 The current study did not replicate these findings whereby inappropriate antibiotics did not increase patient mortality, which may be due to the heterogeneity in patient comorbidities as we demonstrated, as well as the site of infection [26][27][28] and microbiological factors 29 that each influence mortality outcomes. Additionally, patient outcomes may also be influenced by antibiotic adverse events.…”
Section: Discussioncontrasting
confidence: 68%
“…The majority of patients in this and similar studies are at low MRSA risk and this could greatly reduce the number of patients receiving unnecessary MRSA coverage. [ 16 , 36 ] Such an approach would prevent unnecessary MRSA coverage in approximately 25% of the patients in this study. It would only result in failure to cover MRSA when necessary in 3% of the patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…With approximately 50% MRSA prevalence in many regions, local surveillance data and antibiograms become less useful for clinical decisionmaking. Consequently, SSTI prescribing practices vary widely, whereby both under-and over-prescribing of MRSA-active antibiotics occurs frequently [5,[14][15][16][17]. This antibiotic misuse has important implications for both patient outcomes and public health.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of antibiotic prescribing for patients admitted with cellulitis to an Irish district general hospital concluded that there was a significant discrepancy between current clinical practice and international guidelines for the management of cellulitis [ 3 ]. A study in 34 Veterans Affairs Medical Centers in the USA that evaluated antibiotic prescribing for skin and soft tissue infections (cellulitis and abscess) reported that only 14% of patients received guideline-concordant empiric therapy and an appropriate duration of therapy [ 4 ]. In Australia, the National Antimicrobial Prescribing Survey (NAPS, a point prevalence survey of Australian hospitals) indicated that cellulitis/erysipelas was the fifth most common indication for prescribing an antibiotic in public and private hospitals, with an appropriateness of antibiotic choice at 75.3% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%